2021
DOI: 10.1186/s40462-021-00255-9
|View full text |Cite
|
Sign up to set email alerts
|

How animals distribute themselves in space: energy landscapes of Antarctic avian predators

Abstract: Background Energy landscapes provide an approach to the mechanistic basis of spatial ecology and decision-making in animals. This is based on the quantification of the variation in the energy costs of movements through a given environment, as well as how these costs vary in time and for different animal populations. Organisms as diverse as fish, mammals, and birds will move in areas of the energy landscape that result in minimised costs and maximised energy gain. Recently, energy landscapes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 114 publications
0
10
1
Order By: Relevance
“…Regarding interspecific differences, we found that chinstrap penguin samples contained the highest Hg levels in two locations (Livingston I. and Ronge I., Figure 4 ), while we did not find interspecific differences in King George I. These results do not support our prediction that a higher trophic niche could be related to higher mercury level due to bioaccumulation and biomagnification processes, as the gentoo penguin usually has a diet including more fishes and cephalopods, therefore occupying a higher trophic niche, than the chinstrap penguin, which shows a diet with a higher percentage of krill [ 23 , 24 , 27 ]. This coincides with what was described by Brasso et al [ 26 ], which affirms that inter- and intra-specific differences in eggshell membrane mercury concentrations of the same three species of penguins were not related to eggshell δ15N or δ13C values.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…Regarding interspecific differences, we found that chinstrap penguin samples contained the highest Hg levels in two locations (Livingston I. and Ronge I., Figure 4 ), while we did not find interspecific differences in King George I. These results do not support our prediction that a higher trophic niche could be related to higher mercury level due to bioaccumulation and biomagnification processes, as the gentoo penguin usually has a diet including more fishes and cephalopods, therefore occupying a higher trophic niche, than the chinstrap penguin, which shows a diet with a higher percentage of krill [ 23 , 24 , 27 ]. This coincides with what was described by Brasso et al [ 26 ], which affirms that inter- and intra-specific differences in eggshell membrane mercury concentrations of the same three species of penguins were not related to eggshell δ15N or δ13C values.…”
Section: Resultscontrasting
confidence: 82%
“…Differences in habitat use pelagic/offshore in the chinstrap and benthic/inshore in the gentoo and the higher krill consumption of chinstrap [ 27 ] could explain the differences found. Another explanation could involve physiological differences among species such as different capacities for detoxification and elimination of Hg or different absorption-elimination rates.…”
Section: Resultsmentioning
confidence: 99%
“…To create a visual example of energetic measurements from the GPS and ACC methods, we used the inverse distance weighted interpolation tool in ArcGIS (Childs, 2004) to construct four energy landscapes for an individual male and female brown bear on Afognak island. We used the inverse distance weighted interpolation tool as we had a large sample of location data that represented the range of observed values for that energy surface (Masello et al 2021).…”
Section: Energy Landscapementioning
confidence: 99%
“…Analyses of the food consumed by animal species sharing a habitat can facilitate our understanding of the mechanistic processes in a community and the different functions of the organisms in an ecosystem [ 10 ]. Dietary studies give vital insights into foraging behavior [ 11 ] and prey species occurrence and abundance [ 12 ], with implications for understanding environmental change and its impact on wildlife [ 13 , 14 , 15 ]. However, detailed knowledge on the diet of a species can be difficult to obtain, particularly for small, nocturnal, beneath-the-soil, underwater, oceanic or elusive species [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of next-generation sequencing (NGS) has allowed for the identification of prey items of several samples up to the species level in a single sequencing run while upholding the ability to trace each prey back to the sample of origin [ 23 , 24 ]. As a consequence, NGS is increasingly being used for diet studies [ 11 , 25 , 26 ], with feces being the least invasive and most widespread sample type [ 21 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%